Condiciones ergonómicas laborales asociadas a sintomatología músculo-esquelética en el Personal Administrativo de la Universidad Nacional de Loja. - Zula Riofrío, Paul David (2018)
The repeated postural static charge derived from forced and prolonged positions at work causes pathologies known as musculoskeletal disorders, that is an important health problem according to the OMS (2005), and it manifests itself through a set of inflammatory or degenerative lesions of muscles, tendons, nerves, joints, etc, caused or aggravated mainly by work and the effects of the environment in which it develops. The aim of the present research was to determine ergonomic work conditions associated with musculoskeletal symptoms in the administrative staff of the National University of Loja, since Septembre 2017 until February 2018; the type of study was descriptive and transversal, in which 162 people participated, and they were chosen in a simple random way. Also the survey of the Lest Method (2015) and the Nordic questionnaire (2017) was applied. The results show that 91.2% of the population works from feet with an inclination of 1 to 2 hours. The most prevalent symptom is a pain in the lumbar dorsal region with 62%, The ergonomic condition that caused 70.6% of symptomatology in the shoulder were bent positions. In conclusion, the ergonomic posture attitude with inclination caused a statistically significant percentage of musculoskeletal symptomatology. Key words: Ergonomic, musculoskeletal, administrative, symptoms.